Contentious Politics and Conservative Legal Counter-Mobilization of Abortion in Colombia - Beltrán y Puga, Alma (2022)
This essay analyzes the legal mobilization of conservative activists against abortion in Colombia from 2006 to 2020. In the first part, it examines in depth the nullities presented before the Constitutional Court and the State Council by conservative lawyers against reproductive rights of women. In the second part, it studies the demands of unconstitutionality presented before the Constitutional Court to protect life from the moment of conception. All these legal strategies consolidated a legal counter-mobilization to prevent or deny access to abortion. Based in the literature of social movements and their use of law, the article seeks to understand the dynamics of contentious politics where social movements dabble, dividing them in two cycles depending on the legal strategies used and the actors involved. In this context, an explanation is given of why the judicial forum is privileged over the legislative to promote gender backlash with the intention of limiting reproductive rights of women by Catholic activists in Colombia. Their legal strategies are, thus, theoretically understood as a legal counter-mobilization.